Projection of Cooperation Schemes to Address Conflicts Over Spatial Planning Changes in Nusa Dua's Area Management System - Simorangkir, Cavin Ornando; Ramadhan, Givano; Manalu, Triana; Sukran, Muhammad Ali (Department of Geography Education, University of Jember, Indonesia, 2025)
Bali has become Indonesia's leading destination in the global tourism industry, attracting a growing number of investors and privatization efforts. Nusa Dua has been designated as a site for implementing contemporary tourism concepts in Bali, prompting repurposing several areas for new commercial initiatives. The transition has resulted in conflicts among stakeholders over the decades. This study aims to examine methods for addressing conflicts that occur due to Nusa Dua’s spatial changes by identifying the key stakeholders of spatial planning with various interests. The analysis of stakeholders uses qualitative methods that include content analysis, stakeholder analysis, and literature review. DANA software version 1.3.3 is a semi-quantitative analysis used to determine the root cause of the conflicts. The result shows that conflicts over land use decisions are the most contentious in Nusa Dua’s spatial planning policies. This conflict arises due to misunderstanding and misalignment in spatial planning, leading to policy implementation challenges. This study suggests resolving conflicts and enforcing spatial policies by improving stakeholder understanding and communication. A stronger legislative framework for tourism-related development, enhancing stakeholder cooperation schemes, and encouraging sustainable growth are recommended.